Addressing quality and safety in anatomic pathology in low- and middle-income countries - Smith, Stephen M.; Eadara, Amrik; Parkash, Vinita (Frontiers in Medicine, 2022)
The World Health Organization (WHO) has created a sustainable development goal of reducing preventable mortality from cancer in low- and middle-income countries (LMICs) by 30% by 2030. Central to achieving this goal is the creation and maintenance of quality anatomic pathology services (APS). Within the last decade, quality assurance programs and patient safety measures have become a major focus of research for upper middle- and high-income countries (UMHICs), the research of which has led to marked documented improvement in the quality of services provided by laboratories, as well as a decrease in patient safety events. We propose that as APS are developed in LMICs, the lessons learned by UMHICs are necessary to incorporate to produce quality and safe services toward obtaining the aforementioned goal. Here, we propose five strategies that professional organizations and healthcare institutions in UMHICs should consider in partnering with LMICs to accelerate their journey for improved and accurate APS in that setting.